The myth of the renewability in the expansion of agroindustry sucroenergetica - Xavier, Carlos Vinicius; Santos, Luiz Henrique de Melo dos (Universidade de São Paulo. Faculdade de Filosofia, Letras e Ciências Humanas, 2010)
In the context of the expansion of agroindustry sucroenergetica, there is agreat effort of the agroindustry from to relate environmental issues with the activities itself developed, specially the production of ethanol.We observe the formation of a discourse that prioritizes the identification of generation process biofuel as a renewable form of energy production. In contrast to the arguments that emphasizes such renewability or even that identifies in the ethanol of sugar cane the existence of a supposedly clean energy source, we proposed in this article to develop an analysis that reveals this discourse as a myth.Based on an interdisciplinary reflection, we discuss, therefore, some of the territorial impacts resulting from the current ethanol production chain.